2011
DOI: 10.3748/wjg.v17.i9.1126
|View full text |Cite
|
Sign up to set email alerts
|

CT diagnosis of recurrence after pancreatic cancer: Is there a pattern?

Abstract: Specific changes of local and lymph node recurrence can be found in the course of the cardinal peripancreatic vessels. The superior mesenteric artery is the leading structure for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…A significant proportion of these isolated local recurrences may originate from regional lymph node metastases. In a radiological study of computed tomography scans performed for surveillance in 99 patients after pancreatic cancer resection, 17% of patients developed isolated local recurrence, including six patients with isolated lymph node recurrences and 11 patients with lymph node and additional perivascular recurrences . In a study on re‐resection for isolated local recurrence of pancreatic cancer, 41 (72%) of 57 patients with isolated local recurrence proven histologically upon surgical exploration, underwent successful re‐resection associated with a median survival of 26 months after re‐resection .…”
Section: Extent Of Lymphadenectomy and Outcome In Pancreatic Cancermentioning
confidence: 99%
“…A significant proportion of these isolated local recurrences may originate from regional lymph node metastases. In a radiological study of computed tomography scans performed for surveillance in 99 patients after pancreatic cancer resection, 17% of patients developed isolated local recurrence, including six patients with isolated lymph node recurrences and 11 patients with lymph node and additional perivascular recurrences . In a study on re‐resection for isolated local recurrence of pancreatic cancer, 41 (72%) of 57 patients with isolated local recurrence proven histologically upon surgical exploration, underwent successful re‐resection associated with a median survival of 26 months after re‐resection .…”
Section: Extent Of Lymphadenectomy and Outcome In Pancreatic Cancermentioning
confidence: 99%
“…Local recurrence was defined as radiological evidence of intra-abdominal soft tissue in the resection area or along adjacent cardinal visceral vessels that (i) increased in size over time or (ii) had concomitant raised CA 19-9. 30 Biopsy to confirm recurrence was not routinely performed.…”
Section: Postoperative Management and Surveillancementioning
confidence: 99%
“…In pancreatic cancer, the celiac artery (CA) and superior mesenteric artery (SMA) are very important blood vessels to decide the indication for surgery. Some studies have shown that most recurrences were in regions around the CA and SMA, 14,15 and it is considered important in RT planning for LAPC to judge whether to include the CA and SMA lymph node regions. However, because the incidence of CA or SMA involvement in LAPC is high, the gross target volume (GTV) would include those lymph node regions in many patients.…”
Section: Introductionmentioning
confidence: 99%